Debating New Social Media's Political, Social and Cultural Consequences to World's Revolutions - Windah, Andi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2017)
This article discusses a debatable notion that new social media alternately acts as the ground of political revolution or creates new social identity and induces cultural change. Social media sites are information and communication technologies (ICTs) that enable production and sharing of digital content in a mediated social setting. Several statistic reports revealed that these online media showed remarkable usage among citizens of countries across the globe. Having those facts on hand, some experts deduces that the higher usage of social media then more likely to seize the opportunity of increasing engagement in various issues, including tools for nearly all of the worldâ€™s current revolutions. The article also elaborates some counter claims to the notion. As a single click on Facebook group and merely a tweet do not make people politically activated, socially changed and culturally developed. Even though new social media acts as â€œa great mouthpieceâ€, it seems to be an austere logical linkage to say that new social media serve as a way to trigger the worldâ€™s current revolutions. All in all, new social media platforms can be utilized by their users with any kind of purposes especially in terms of providing fast and quick informational system. Artikel ini membahas gagasan yang cukup hangat diperdebatkan oleh kalangan intelektual dunia bahwa sosial media baru mendasari munculnya revolusi politik, menciptakan identitas sosial jenis baru dan menginduksi perubahan budaya. Situs media sosial adalah teknologi informasi dan komunikasi (TIK) yang memungkinkan konten digital diproduksi dan didistribusikan dalam lingkungan sosial termediasi. Beberapa laporan statistik mengungkapkan bahwa penggunaan media online oleh warga negara dunia menunjukkan angka yang luar biasa. Fakta-fakta inilah yang membuat beberapa ahli menyimpulkan bahwa penggunaan media sosial yang cukup tinggi menaikkan kesempatan keterlibatan warga dunia secara signifikan dalam berbagai isu, termasuk keterlibatan dalam semua revolusi di dunia saat ini. Artikel ini juga menguraikan beberapa klaim bertentangan dengan gagasan tersebut. Bahwa satu klik pada halaman Facebook dan sebuah cuitan pada Twitter tidak membuat orang aktif secara politik, berubah secara sosial dan budaya. Meskipun media sosial baru dapat dikategorikan sebagai